Lead in Plants: Sources, Toxicity, and Tolerance Mechanisms (International Journal of Food and Nutritional Sciences, 2021)
Lead (Pb) stands out as the most prevalent heavy metal contaminant in the environment. While plants absorb Pb from their surroundings, it is not a vital element for their growth. Pb is notably abundant, especially in the soil of roadside fields due to emissions from automotive exhaust. Additionally, it is present in fields with a prolonged history of fertilization using fertilizers that contain Pb as an impurity. Numerous sources contribute to Pb contamination, including soil, water, air, batteries, toys, cans, and fertilizers. In this review, our focus is on examining the impact of Pb on plant growth and development, along with exploring the mechanisms plants employ to endure lead toxicity. Pb ranks among the most frequently encountered heavy metals in terrestrial and aquatic ecosystems, entering through various natural and human-induced sources. The accumulation of Pb in plants is dose-dependent and leads to toxicity. The uptake of Pb increases the concentration of Mn, while reducing the total concentrations of most other minerals, including K, Ca, Na, P, Mg, Zn, Fe, and Cu. Plant exposure to Pb limits the sprouting and development of young seedlings.